Imaging of Surgical Free Flaps in Head and Neck Reconstruction - McCarty, J.L.; Corey, A.S.; El-Deiry, M.W.; Baddour, H.M.; Cavazuti, B.M.; Hudgins, P.A. (American Journal of Neuroradiology, 2019)
SUMMARY: Head and neck surgical reconstruction is complex, and postoperative imaging interpretation is challenging. Surgeons now use microvascular free tissue transfer, also known as free flaps, more frequently in head and neck reconstruction than ever before. Thus, an understanding of free flaps, their expected appearance on cross-sectional imaging, and their associated complications (including tumor recurrence) is crucial for the interpreting radiologist. Despite the complexity and increasing frequency of free flap reconstruction, there is no comprehensive head and neck resource intended for the radiologist. We hope that this image-rich review will fill that void and serve as a go to reference for radiologists interpreting imaging of surgical free flaps in head and neck reconstruction.ALTanterolateral thighCECTcontrast-enhanced CTFFfree flapH&Nhead and neckSCCsquamous cell carcinoma